Climate change and bicycling. How bicycling advocates can help craft comprehensive Climate Action Plans. - (:unkn) unknown (My University, 2010)
Bicycling advocates can help shape Climate Action Plans to include bicycling policies. Using case studies and examples from existing plans, this report examines: 1. how pro-bicycling policies have been written into the Climate Action Plans of states, cities, and universities, 2. examples of plans that include bicycling, 3. how bicycling advocates can best support these efforts, and 4. how to ensure that governments follow through on the promises made in their plans. (D.F.)
Keywords: Fahrradverkehr; Öffentlichkeitsarbeit; Individualverkehr; Verkehrspolitik; Verkehrsplanung; Radverkehrsförderung; Fahrradförderung; Klimaschutz; Nachhaltige Mobilität; Emissionsminderung; Radverkehrsplanung